1988
DOI: 10.2343/geochemj.22.265
|View full text |Cite
|
Sign up to set email alerts
|

Radon and helium anomalies in mud volcanoes from northern Apennines(Italy). A tool for earthquake prediction.

Abstract: Rn-222 and total helium contained in saline waters and associated gaseous fluids from a series of mud volcanoes occurring along the northeastern border of the Apennine chain (northern Italy) have been determined as possible precursors of local earthquakes. Investigations spanned over about one year (May 1986-May 1987 during which a series of low to medium-magnitude (M = 3-4.5) local earth quakes occurred with distinct focus. Spike-like Rn anomalies were almost systematically observed a short time (hours to few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Active mud volcanoes in the Ionian Sea and elsewhere could provide information on the seismic cycle of nearby faults [e.g. Bouleguè et al, 1985;Gorgoni et al, 1988;Martinelli et al, 1991Martinelli et al, , 1995Gulijev and Feizullayen, 1997;Milkov, 2000;Dimitrov, 2002;Kopf, 2002, Mazzini andEtiope, 2017] and could therefore be important targets for future geochemical monitoring [Cuffaro et al, 2019], as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Active mud volcanoes in the Ionian Sea and elsewhere could provide information on the seismic cycle of nearby faults [e.g. Bouleguè et al, 1985;Gorgoni et al, 1988;Martinelli et al, 1991Martinelli et al, , 1995Gulijev and Feizullayen, 1997;Milkov, 2000;Dimitrov, 2002;Kopf, 2002, Mazzini andEtiope, 2017] and could therefore be important targets for future geochemical monitoring [Cuffaro et al, 2019], as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Santi, 1896; Pellegrini et al, 1982;Gorgoni et al, 1988). Other investigations (Gorgoni, 2003) have shown that the activity of the mud volcanoes is influenced by local seismicity, some days before the occurrence of rather strong earthquakes.…”
Section: Excursion Notesmentioning
confidence: 97%
“…The mud volcanoes show the presence of permeable structures, tectonically active, and their study can provide useful "windows" on how fluids move through the upper crust and the sedimentary cover towards the surface. Water analysis emitted by salse highlighted connate origin of such fluids dominated by sodium-chloride component (Gorgoni et al, 1988). Extruded gas is chemically composed by 93% methane, 5% nitrogen, 2% oxygen, 1% carbon dioxide, and about 660 ppm of ethane (analysis carried out by the Authors at the mud volcano complex, Stop 1.6, in June 2013).…”
Section: Geochemical Characteristic Of Mud Volcanoesmentioning
confidence: 99%
See 2 more Smart Citations